Comparative evaluation of BISAP score and computed tomography severity index as a predictor for severity of acute pancreatitis - Jingoniya, Narottam K.; Yadav, Bhanwar L.; Verma, Pradeep K.; Bansal, Somendra; Gupta, Shalu (International Surgery Journal, 2022)
Background: Acute severe pancreatitis is life threatening condition with organ failure, pancreatic necrosis, infections, and death. Multiple factor scoring systems are used for triage decision to manage of acute pancreatitis according to severity. Our purpose of this study was to assess the efficiency of the bedside index of severity in acute pancreatitis (BISAP) score and computed tomography severity index (CTSI) scoring system to predict severity of acute pancreatitis. Methods: This hospital based observational, prospective study was conducted from 01 March 2019 to May 2020. An inclusion criterion was patients admitted with diagnosis of acute pancreatitis. Comparative analysis was done for BISAP and CTSI in terms of severity and mortality. Results: The mean age was 44.7±16.2 years and male to female ratio was 1.9:1. BISAP score had 91.7% sensitivity and 51.4% specificity in predicting severity of acute pancreatitis with 38.6% positive predictive value (PPV) and 94.9% negative predictive value (NPV). CTSI score had 95.8% sensitivity and 44.4% specificity in predicting severity of acute pancreatitis with 36.5% PPV and 96.9% NPV. The area under curve (AUC) for BISAP and CTSI was 0.853 (95% CI: 0.769–0.937) and 0.901 (95% CI: 0.831– 0.97) respectively. Conclusions: We conclude that BISAP score is better predictor of severity and mortality in acute pancreatitis and can safely be utilized to predict severity of acute pancreatitis in situations where use of CT is limited due to cost factor or availability, especially in rural areas. BISAP score is a scoring system that can be easily calculated with available clinical data even in small hospital setups.